2010
DOI: 10.4028/www.scientific.net/amm.20-23.1458
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Pyroshock Responses of a Conical Shell

Abstract: In space engineering, pyroshock (or pyrotechnical shock) environments induced by pyrotechnical devices are severe for space hardware, especially the inner electrical components. Thus pyroshock responses need to be well considered in the design and manufacture of a space structure or system. Because of the lack of efficient analytical technique, laboratory tests are of importance at present. This paper experimentally studies the pyroshock responses of a conical aeroshell. Two experiments were performed by ignit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Mao et al [ 3 ] showed that along the axial distance from the pyroshock sources, the conical aeroshell has decaying characteristics in its responses, both in time and frequency domains. Takashi et al [ 4 ] showed that the out‐of‐plane accelerations were dominant than that in any other directions.…”
Section: Introductionmentioning
confidence: 99%
“…Mao et al [ 3 ] showed that along the axial distance from the pyroshock sources, the conical aeroshell has decaying characteristics in its responses, both in time and frequency domains. Takashi et al [ 4 ] showed that the out‐of‐plane accelerations were dominant than that in any other directions.…”
Section: Introductionmentioning
confidence: 99%
“…Mao et al showed that the responses of conical aeroshell have decaying characteristics along the axial distance from the pyroshock sources both in time and frequency domains. Mao et al presented various techniques in time domain as well as frequency domain to predict structural responses under special dynamic environments.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the design stage of a new aerospace system, the details of the structures, layouts and installations of the components may be unknown. Test simulations can not be undertaken with high fidelities, as indicated in Ref [6]. Thus, numerical techniques are much necessary to be developed for pyroshock responses prediction.…”
Section: Introductionmentioning
confidence: 99%